Does the efficacy of parent-child training depend on maternal symptom improvement?: Results from a randomized controlled trial on children and mothers both affected by attention-deficit/hyperactivity disorder (ADHD) - Häge, Alexander; Alm, Barbara; Banaschewski, Tobias; Becker, Katja; Colla, Michael; Freitag, Christine; Geissler, Julia; von Gontard, Alexander; Graf, Erika; Haack-Dees, Barbara; Hänig, Susann; Hennighausen, Klaus; et al. (European child & adolescent psychiatry, 2018)
Multimodal treatment of children with ADHD often includes parent-child training (PCT). However, due to the high heritability, parents of children with ADHD are frequently also affected by the disorder, which is likely to constitute a significant barrier to successful treatment of the child. This secondary analysis of our randomized controlled multicentre AIMAC trial (ADHD in mothers and children) investigates whether children's outcomes following parent-child training in combination with maternal ADHD treatment depend on maternal symptom improvement. In a first step focusing on treatment of maternal ADHD, 144 mothers of mother-child dyads were randomized to multimodal ADHD treatment (group psychotherapy plus methylphenidate) or clinical management (mainly supportive counselling). After 12 weeks (T2), a 12-week PCT program (T2-T3) for all mother-child dyads was added to treat children's ADHD. Maternal symptomatology (CAARS-O:L; SCL-90-R) and children's externalizing symptoms (ADHD-ODD Scale, SDQ) were repeatedly assessed (T1 = baseline, T2, T3). Effects of changes in maternal symptomatology (T1-T2) on the change in children's symptom scores (T1-T3) were analysed using a general linear model, controlling for baseline scores, study centre, and maternal treatment group. 125 mother-child dyads were analysed. Mothers showed significant improvements in ADHD symptoms and overall psychopathology [CAARS-O:L ADHD index: mean - 3.54, SE 0.74 p < 0.0001; SCL-90-R Global Severity (GS): mean - 11.03, SE 3.90, p = 0.0056]. Although children's externalizing symptoms improved significantly (ADHD-ODD Scale: mean - 4.46, SE 0.58, p < 0.0001), maternal improvement had no effect on children's outcomes after Bonferroni-Holm correction for multiple testing. The findings do not support our hypothesis that children's outcomes following PCT for ADHD depend on maternal symptom improvements.Trial register CCT-ISRCTN73911400.
Gesehen am 20.04.2020